Investigaton of antimicrobial prescribing patterns at Themba Hospital, Kabokweni - Danysz, Karolina Z (University of Limpopo (Medunsa), 2010)
Introduction: Antibiotics are among the most commonly prescribed drugs in the hospital setting. Because of an overall rise in health care costs, lack of uniformity in drug prescribing and the emergence of antibiotic resistance, monitoring and control of antibiotic use are of growing concern and strict antibiotic policies and prescribing guidelines are warranted. The aim of the study was to monitor the antibiotic prescriptions in a general outpatient setting in a rural regional hospital in Mpumalanga and to determine the impact of an education intervention on the prescribing patterns and adherences to the EDL/STD Method: Randomly selected adult outpatients files, at Themba Hospital, Mpumalanga, were selected to review the antibiotic prescribing patterns. The antibiotic prescriptions, diagnosis or symptom complex, and category of prescriber were recorded. The antibiotic prescriptions were cost according to the 2007 Hospital price list. Prescriptions were recorded in two phases; Phase 1; September, October and November 2006 and again January, February and March 2007 for Phase 2. Lectures on antibiotic prescribing, the use of the EDL/STG and the risk of antibiotic resistance were provided to all medical doctors in the first two weeks of January 2007. The prescription patterns, compliance with EDL/STG and the cost of the pre and post lectures were compared. Results: During the six-month study, a total of 1021 (Phase 1 = 505; Phase 2 = 520) prescriptions were reviewed and of those, 368 [Phase 1 = 230(46%); Phase 2 = 138 (27%)] prescriptions contained one or more antibiotics. Although the total number of antibiotics prescribed decreased from 338 in Phase 1 to 172 in Phase 2 the non-adherent to the EDL/STD for each antibiotic for the different diagnoses increased from 90% to 98% in Phases 1 and 2 respectively. There was no improvement in non-adherent prescriptions from the Community Medical Officers (CMO) and the Medical Interns after the lecture. The total antibiotic cost for the study period was R4 235.29 the calculated cost as per STG for the different diagnoses was R1 485.02 a decrease of 285% Conclusion: The number of prescriptions with antibiotics and the number of antibiotics decreased after the lecture. The antibiotics were not prescribed according to the EDL/STD. The lectures ix had no impact on the EDL/STG adherence. The EDL/STG should be included in the teaching and learning of medical students as the junior staff prescribed the most nonadherent antibiotic prescriptions and a once off in-service lecture had little impact. Prescribing according to the STG could have a significant impact in decreasing the cost of antibiotics.
Keywords: antimicrobial